Phylogenetic and Structural Diversity in the Feline Leukemia Virus Env Gene - Watanabe, Shinya (Public Library of Science, 2013)
Feline leukemia virus (FeLV) belongs to the genus Gammaretrovirus, and causes a variety of neoplastic and non-neoplastic diseases in cats. Alteration of viral env sequences is thought to be associated with disease specificity, but the way in which genetic diversity of FeLV contributes to the generation of such variants in nature is poorly understood. We isolated FeLV env genes from naturally infected cats in Japan and analyzed the evolutionary dynamics of these genes. Phylogenetic reconstructions separated our FeLV samples into three distinct genetic clusters, termed Genotypes I, II, and III. Genotype I is a major genetic cluster and can be further classified into Clades 1–7 in Japan. Genotypes were correlated with geographical distribution; Genotypes I and II were distributed within Japan, whilst FeLV samples from outside Japan belonged to Genotype III. These results may be due to geographical isolation of FeLVs in Japan. The observed structural diversity of the FeLV env gene appears to be caused primarily by mutation, deletion, insertion and recombination, and these variants may be generated de novo in individual cats. FeLV interference assay revealed that FeLV genotypes did not correlate with known FeLV receptor subgroups. We have identified the genotypes which we consider to be reliable for evaluating phylogenetic relationships of FeLV, which embrace the high structural diversity observed in our sample. Overall, these findings extend our understanding of Gammaretrovirus evolutionary patterns in the field, and may provide a useful basis for assessing the emergence of novel strains and understanding the molecular mechanisms of FeLV transmission in cats.